Rock Mass Loss on a Nunatak in Western Dronning Maud Land, Antarctica. Issue 1 (1st February 2016) - Hedding, D. W.; Hansen, C. D.; Nel, W.; Loubser, M.; Le Roux, J. J.; Meiklejohn, K. I.
ABSTRACT: This paper presents the first rock mass loss data for uncut clasts from continental Antarctica. A rock mass loss experiment using doleritic rock samples was conducted over a seven-year period, between 2008 and 2014, at the Vesleskarvet nunataks, Western Dronning Maud Land. The data show that approximately 10% of clasts suffered a mass loss that is an order of magnitude greater than the remaining 90% of clasts. Thus, the observed rock mass loss is suggested to occur in a series of events that are impossible to predict in terms of frequency and/or magnitude. However, extrapolating from the data obtained during the seven-year period indicates that rates of mass loss are slow and of the order of 1% per 100 years. Direct erosion by wind (including abrasion) as well as mechanical and chemical weathering are suggested to be responsible for rock mass loss. Rock properties, the weathering environment, and a lack of available moisture may be contributing factors to the slow rate of rock decay. This paper suggests that in this area of Antarctica, the slow rate of rock mass loss increases the longevity of existing periglacial landforms such as patterned ground and blockfields, but inhibits development of new patterned ground through the slow production of fines.